ISLAM DAN LIBERALISME - Ahmad Fauzi Muslim Noor Sya’ban; Ahmad Munawar; Alma Ashofi Izzani; Asep Abdul Muhyi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Islam and liberalism are two paradigms of thought that have different origins, values and principles. Conflicts between Islam and liberalism often arise in various political, social and religious contexts, due to differences in views on religious authority, individual freedom, the role of the state and social values. However, the relationship between Islam and liberalism also reflects the complexity of social and political dynamics involving interaction, dialogue and cooperation between the two paradigms of thought. The study of Islam and liberalism shows the importance of understanding the history, context, and variations of thought in modern Muslim societies. Thus, efforts to achieve better understanding and harmony between Islam and liberalism require an approach that is inclusive, critical, and based on cross-cultural and religious dialogue.